Global Height Trends and the Determinants of Anthropometric Welfare, 1810s - 1980s - Matthias Blum; Jörg Baten (Verein für Socialpolitik, 2010)
The aim of our study is to include all the information on male stature which has been estimated in previous research. 152 countries can be taken into account. Height estimates will be presented on a decadal basis. We study the development in each world regions. When the first era of globalization boomed during the late 19th century, the New World food exporting economies could, for example, have lost some of their initial height advantage. This study will also focus on one of the most important questions in anthropometric history: what determines heights? Apart from general purchasing power and the disease environement, we would expect heights to be also influenced by the availability of high-quality food stuffs (such as milk and meat). Those food items have been identified in previous research as having a bottleneck-type importance for anthropometric values due to their content of high-quality proteins and calcium. Apart from the nutritional value, historical populations needed large amounts of protein to generate antibodies to fight infectious disease (as well as those in today's Less Developed Countries).
Keywords: N00; D60; N01; 330